Intervensi Republik Vanuatu Dalam Persoalan Papua, Perspektif Hukum Internasional - Andi M Anshari Yusri; Lucia Charlota Octovina Tahamata; Richard Marsilio Waas (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: The principle of Non-Intervention as a form of recognition of international law. Starting from the principle of Non-Intervention in 2016, one of the countries in the Pacific Ocean, the Republic of Vanuatu for the first time raised the issue of human rights violations in Papua Province at the UN General Assembly.Purposes of the Research: This writing aims to understand and find out the regulations regarding the intervention of the republic of Vanuatu in the province of Papua, from an international legal perspectiveMethods of the Research: The research method used is a normative juridical research method as well as sources of legal materials which include legal materials, primary, secondary legal materials and tertiary legal materials. The collection of legal materials is done through literature study and analysis.Results of the Research: The results of this study explain that the regulation of intervention in international legal instruments has been strictly and precisely regulated in international law. This is contained in the provisions of the United Nations Charter, namely in article 2 paragraph (7) which explains that every country in conducting international relations is prohibited from intervening in the domestic affairs of other countries. In the United Nations Charter article 2 paragraph (7) the intervention carried out by the State of Vanuatu is an attitude and statement that is not justified in international law because it is contrary to the principles of international law.